Efectos del camuflaje en la salud mental de las personas con el trastorno del espectro autista - Augusto Della Torre, Maria Luciana (2021)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder whose prevalence is increasing. In addition, it is accompanied by a phenomenon known as camouflaging, which is used by autistic people as a tool to mask social challenges in neurotypical settings, thus generating negative effects on their mental health. The aim of this work is to identify recent findings about the effects of camouflaging on people with ASD. A database search was conducted according to some of the PRISMA Guidelines (Urrútia & Bonfill, 2010). The databases searched were PubMed, ResearchGate, BioMed and SAGE Journal, and only research conducted between 2015 and 2021 was considered. A total of 7 research papers that assessed camouflaging and mental health on autistic people were selected. The evidence suggests camouflaging occurs in both men and women; however, it is more prevalent on women with ASD. This results in late diagnoses for such population, which impacts negatively on their mental health.